Parasternal intercostal thickening at hospital admission: a promising indicator for mechanical ventilation risk in subjects with severe COVID-19 - Helmy, Mina A.; Milad, Lydia M.; Hasanin, Ahmed M.; Mostafa, Maha; Mannaa, Asser H.; Youssef, Marianne M.; Abdelaziz, Mahmoud; Alkonaiesy, Ramy; Elshal, Mamdouh Mahmoud; Hosny, Osama (Journal of clinical monitoring and computing, 2023)
We aimed to evaluate the ability of parasternal intercostal thickening fraction (PIC TF) to predict the need for mechanical ventilation, and survival in subjects with severe Coronavirus disease-2019 (COVID-19). This prospective observational study included adult subjects with severe COVID-19. The following data were collected within 12 h of admission: PIC TF, respiratory rate oxygenation index, P aO 2 / F iO 2 ratio, chest CT, and acute physiology and chronic health evaluation II score. The ability of PIC TF to predict the need for ventilatory support (primary outcome) and a composite of invasive mechanical ventilation and/or 30-days mortality were performed using the area under the receiver operating characteristic (AUC) analysis. Multivariate analysis was done to identify the independent predictors for the outcomes. Fifty subjects were available for the final evaluation. The AUC (95% confidence interval [CI]) for the right and left PIC TF ability to predict the need for ventilator support was 0.94 (0.83–0.99), 0.94 (0.84–0.99), respectively, with a cut off value of > 8.3% and positive predictive value of 90–100%. The AUC for the right and left PIC TF to predict invasive mechanical ventilation and/or 30 days mortality was 0.95 (0.85–0.99) and 0.90 (0.78–0.97), respectively. In the multivariate analysis, only the PIC TF was found to independently predict invasive mechanical ventilation and/or 30-days mortality. In subjects with severe COVID-19, PIC TF of 8.3% can predict the need to ventilatory support with a positive predictive value of 90–100%. PIC TF is an independent risk factor for the need for invasive mechanical ventilation and/or 30-days mortality.